AN ANALYSIS OF PLOT IN FROZEN MOVIE - Ellen Gladys Yunita Manueke; Della Christina Pontoan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The inclusion of plot is a significant component inside narrative literary works. Plots inside literary works, films, novels, or other storylines encompass a series of interconnected events, where each occurrence exerts an influence on subsequent developments. The film is currently regarded as a potent means of mass communication due to its audio-visual characteristics, including its ability to present vivid sights and sounds. Movies have the ability to convey a significant amount of information within a limited duration through the use of visual imagery and auditory elements. This study is to conduct an analysis of the utilization of the storyline in the cinematic production of Frozen. The objective of this analysis is to provide a description of the narrative structure and events depicted in the film. The present study employed a descriptive qualitative approach. Initially, the author classifies several components of a sentence, conversation, and scene. Subsequently, proceed to search for, analyze, and interpret the text in order to derive the plot structure in alignment with the relevant theoretical framework. Based on the findings of the analysis, it can be concluded that the film encompasses the complete narrative structure, including the exposition, rising action, climax, and falling action. The film concludes with a conclusion that is not open-ended. The film exhibits a forward-moving or progressive narrative structure. The authors express their anticipation that the outcomes of this study will prove advantageous to subsequent researchers with an inclination towards investigating the intersection of literature and film, particularly with regard to narrative structure.